African philosophy and the African Renaissance: a quest for a true humanity - Sesanti, Simphiwe O (My University, 2021)
Among the devastating consequences of slavery and colonialism inflicted by the Western world on the African world was the dehumanisation of the African people. In a manisfestation of a superiority complex, the Western world imposed on the rest of the world its values, and measured everything by its standards. Included in this was the meaning of being “human”. In a relentless struggle to regain their independence, Africans involved in the liberation struggle recognised that their struggle was incomplete if it was going to be limited to flag and national anthem independence. For African freedom to be complete, Africans would have to regain their cultural freedom so that they would be able to measure their humanity on their own terms. This quest for cultural freedom is what came to be known as the “African Renaissance”. But just as Africans were determined to regain their freedom, so was the determination of the colonialiststo concede this independence on their own terms, resulting in setbacks and a protracted struggle on the part of the African people. When South Africa became a democracy in 1994, some South African intellectuals, politicians and academics revisited the African Renaissance idea and hosted an international conference to examine strategies of achieving this elusive quest. Among the intellectual tools identified to accomplish this task were political philosophies. This study, therefore, was inspired by the 1998 African Renaissance conference. It is an examination of the role that African philosophy can play in realising the African Renaissance vision. More specifically, the study examined how indigenous African cultural notions such as “Ancestor-Reverence”, “family” and “consensus” can bring this about. The study has established that the African Renaissance vision, in line with the ideology of Pan-Africanism, does not only seek to restore Africans’ humanity damaged by slavery and colonialism, but also seeks to re-humanise the whole of humanity because in the process of dehumanising Africans, enslavers and colonialists were dehumanised, too
A thesis submitted to the Faculty of Humanities, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Doctor of Philosophy, 2021